APS C++ User's Library - Letichevsky, A.; Letichevsky, A.Jr.; Peschanenko, V. (Інститут програмних систем НАН України, 2008)
The general information about the APS algebraic programming system (terms rewriting system) is briefly described in the present article. It is justified practical necessity of creation of APS C++ User’s Library, its conception is presented and its main functions are listed. Also it is mentioned few words about the translator APLAN-C++.